Prevalence and risk factors of stroke-related sarcopenia at the subacute stage: A case control study - Yao, Ruihong; Yao, Liqing; Rao, Amin; Ou, Jibing; Wang, Wenli; Hou, Qinzhi; Xu, Chunyan; Gao, Bu-Lang (Frontiers in Neurology, 2022)
Purpose To investigate the prevalence and risk factors of stroke-related sarcopenia (SRS) in hospitalized patients receiving rehabilitation treatment. Methods Approximately, 259 patients with stroke that satisfied the inclusion and exclusion criteria were consecutively recruited between June 2020 and July 2022. The epidemiologic data, history, clinical data, and measured data of the skeletal muscle index were collected. The patients were divided into the sarcopenia and non-sarcopenia group for comparison and analysis with the univariate and multivariate analysis. Results SRS was presented in 121 (46.7%) patients with a mean age of 59.6 ± 9.7 years, including 42 women and 79 men. Multivariate logistic regression analysis revealed the following parameters to be significant (p < 0.05) risk factors for SRS: college degree or above (OR, 2.1, 95% CI, 1.1–4.1), ICU stay (OR, 1.7, 95% CI, 1.06–2.8), pneumonia (OR, 1.9, 9% CI, 1.1–3.6), walking ability (OR, 2.6, 95% CI, 1.5–4.6), cognitive impairment (OR, 1.8, 95%, 1.1–2.9), aphasia (OR, 2.1, 95% CI, 1.2–3.5), nasogastric feeding (OR, 3.7, 95%, 1.9–7.3), age (OR, 1.04, 95% CI, 1–1.1), and creatine kinase (OR, 1.1, 95% CI,0.9–1.2). Conclusions Older age, light weight, severer clinical conditions, cognitive impairment, and significantly decreased levels of albumin, RAG, creatinine, uric acid, red blood cell count, hemoglobin, prealbumin, iron, and creatine kinase are more significantly present in patients with SRS compared with those without SRS.